2011
DOI: 10.5194/hess-15-2747-2011
|View full text |Cite
|
Sign up to set email alerts
|

A simple 2-D inundation model for incorporating flood damage in urban drainage planning

Abstract: Abstract. An urban inundation model was developed and coupled with 1-D drainage network model (EPA-SWMM5). The objective was to achieve a 1-D/2-D coupled model that is simple and fast enough to be consistently used in planning stages of urban drainage projects. The 2-D inundation model is based on a non-standard simplification of the shallow water equation, lays between diffusion-wave and full dynamic models. Simplifications were made in the process representation and numerical solving mechanisms and a depth s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…When water begins to overflow it becomes a 2D phenomenon and the use of a 2D model is more suitable. Thus, 2D numerical models were successfully applied for flood modelling [14][15][16]; the discharge is used as upstream boundary condition of the main river channel and then a 2D simulation is performed. Nowadays there is a wide availability of numerical models with different capabilities and from different developers; some models are free while others require the purchase of a licence.…”
Section: Introductionmentioning
confidence: 99%
“…When water begins to overflow it becomes a 2D phenomenon and the use of a 2D model is more suitable. Thus, 2D numerical models were successfully applied for flood modelling [14][15][16]; the discharge is used as upstream boundary condition of the main river channel and then a 2D simulation is performed. Nowadays there is a wide availability of numerical models with different capabilities and from different developers; some models are free while others require the purchase of a licence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that urban catchments, characterised by a fast hydrological response due to both low interception and infiltration, are highly sensitive to small-scale spatial and temporal variability of the precipitation field (Bell and Moore, 2000;Einfalt et al, 2004;Gires et al, 2013) In the past, a lot of studies have addressed requirements and approaches for flood modelling (Schmitt et al, 2004;Balmforth and Dibben, 2006;Parker et al, 2011;Pathirana et al, 2011;Priest et al, 2011;Neal et al, 2012;Ozdemir et al, 2013). More recently, studies have shown the impact of rainfall variability on hydrodynamic models outputs (Gires et al, 2012;Liguori et al, 2012;Vieux and Imgarten, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cost-benefit analysis could be considered, but this would require damage assessment (cf. Pathirana et al, 2011;Jonkman et al, 2008).…”
Section: Discussionmentioning
confidence: 97%